(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2021)
In the current work, we use the (M,N)-Lucas Polynomials to introduce a new families of holomorphic and bi-Prestarlike functions defined in the unit disk O and establish upper bounds for the second and third coefficients of the Taylor-Maclaurin series expansions of functions belonging to these families. Also, we debate Fekete-Szeg¨o problem for these families. Further, we point out several certain special cases for our results.